Tantangan Distribusi dan Ketergantungan BBM dalam Mewujudkan Ketahanan Energi Pulau Wetar - Akbar, Amany Zhafira; Yoesgiantoro, Donny; Sasongko, Nugroho Adi (PendIPA Journal of Science Education, 2026)
Energy security is a strategic element in supporting sustainable development and national security, particularly in Indonesia's outermost islands. Wetar Island in Southwest Maluku Regency faces serious challenges in the form of high dependence on fuel oil and limited energy distribution systems. This study aims to conduct an in-depth analysis of the challenges of distribution and dependence on BBM and their impact on the energy security of Wetar Island. The study uses a qualitative approach with a case study method through analysis of policy documents, energy institution reports, and related scientific studies. The results of the study show that the dominance of BBM, logistical obstacles due to geographical conditions, and high energy costs have led to low resilience in the local energy system. In addition, the limited use of renewable energy has increased the region's energy vulnerability. This study emphasises the need for energy diversification, strengthening of local infrastructure, and integration of central and regional policies in order to achieve sustainable energy security for Wetar Island.